A community based funding model to conserve New Zealand's built heritage : a thesis presented in partial fulfilment of the requirements for the degree of M.Phil in Resource and Environmental Planning at Massey University - Fill, Barbara (Massey University, 1997)
This thesis examines the role of community groups in the conservation of New Zealand's built heritage through access to discretionary funding and professional conservation advice. It will be argued that the provision of funding and conservation advice to community groups by those agencies with a statutory responsibility for conserving New Zealand's built heritage is currently inadequate and that there is a clear role for a non-government funding agency to provide funding to community groups wishing to conserve buildings they have identified within their community. However, it will be contended that funding alone is not enough and that appropriate conservation advice is necessary if national and international conservation standards are to be met and buildings conserved for future generations. A review of the literature pertaining to the different concepts, values and significance of the built heritage ascribed to it by professionals and the community has been carried out. Legislation in New Zealand namely the Resource Management Act 1991 and the Historic Places Act 1993 has been examined and the roles of the central agencies under these two pieces of legislation have been identified. A number of community empowerment attributes are identified and are used to evaluate the effectiveness of the community based funding model developed by the Lottery Environment and Heritage Committee (a distribution committee of the New Zealand Lottery Grants Board), which provides funding to community groups for the conservation of historic buildings. A case study is used to demonstrate the effectiveness of this process.
Keywords: Historic building conservation; Citizen participation; New Zealand heritage; Historic building funding; Historic Places Act 1993